Investigating and Comparing Some Consumption-Based Asset Pricing Models: The Case of Iran - Mohammadzadeh, Azam; Tash, Mohammad Nabi Shahiki; Roshan, Reza (International Journal of Economics and Financial Issues, 2016)
Studies of last two decades refer to limits on the classical models of asset pricing such CAPM and CCAPM. In this article we make adjustments in CCAPM model and have been estimated modified models for the economy of Iran from 1988 to 2011. These models are HCCAPM and SCCAPM that in them investigated the implications of novel classes of preferences for the behavior of asset prices. In SCCAPM model utility function is a function of consumption and savings. In HCCAPM model utility function is a function of nonhousing and housing consumption. In this article estimated Euler equations for these preferences with GMM. We employ comparison criteria Hansen and Jagannathan (1997) HJ-distance for compare these models. Our empirical results indicated that economic factors are patient and very risk averse. Elasticity of substitution between housing service consumption and nonhousing service consumption is positive. However the HCAPM and SCCAPM have the explanatory power stock returns but compared to CCAPM have less performance or introducing housing and saving into the consumption-based models does not always improve the models' performance. Results of SCCAPM suggested that the preference for saving in Iran is economically significant. Keywords: Asset pricing, preferences, saving, Saving-based asset-pricing, housing service consumption JEL Classifications: G10, G11, G12